2003
DOI: 10.1073/pnas.1331721100
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary deterioration of the vomeronasal pheromone transduction pathway in catarrhine primates

Abstract: Pheromones are water-soluble chemicals released and sensed by individuals of the same species to elicit social and reproductive behaviors or physiological changes; they are perceived primarily by the vomeronasal organ (VNO) in terrestrial vertebrates. Humans and some related primates possess only vestigial VNOs and have no or significantly reduced ability to detect pheromones, a phenomenon not well understood at the molecular level. Here we show that genes encoding the TRP2 ion channel and V1R pheromone recept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
215
0
2

Year Published

2004
2004
2015
2015

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 240 publications
(224 citation statements)
references
References 53 publications
6
215
0
2
Order By: Relevance
“…Although they have an intact accessory olfactory system, there is little evidence that it has a similar function in platyrrhines (with the exception of callitrichids). Catarrhines lack an intact AOS and show a significant reduction in olfactory behavior Meisami and Bhatnagar, 1998;Liman and Innan, 2003;Zhang and Webb, 2003).…”
Section: Mob Size and Intrasexual Competitionmentioning
confidence: 99%
See 3 more Smart Citations
“…Although they have an intact accessory olfactory system, there is little evidence that it has a similar function in platyrrhines (with the exception of callitrichids). Catarrhines lack an intact AOS and show a significant reduction in olfactory behavior Meisami and Bhatnagar, 1998;Liman and Innan, 2003;Zhang and Webb, 2003).…”
Section: Mob Size and Intrasexual Competitionmentioning
confidence: 99%
“…Some platyrrhines are polymorphic for this trait: in several species, 50 -60% of females are trichromatic, while males are not (Jacobs, 1995;Jacobs and Deegan, 2001). As there is a concomitant reduction of the size, presence, and function of haplorhine olfactory structures, it has been argued that some of the functions of the strepsirrhine olfactory system may be served by the visual system in these taxa (Barton et al, 1995;Barton and Aggleton, 2000;Barton, 2001;Laska et al, 2003;Liman and Innan, 2003;Zhang and Webb, 2003;Gilad et al, 2004). Visual communication might be superior to olfaction because it allows conspecifics to identify individuals and assess social situations without coming into physical contact with odorants.…”
Section: Trade-off Hypothesis Of Olfactory and Visual Communicationmentioning
confidence: 99%
See 2 more Smart Citations
“…In human, the entire V1R repertoire, including functional genes and pseudogenes, has approximately 200 members. However, the functional V1R repertoire is small, with only four open reading frames in most individuals Zhang and Webb 2003) . Grus et al (2005) identified functional V1R genes from five orders of placental and marsupial mammals ( Table 1 ).…”
Section: The V1r Gene Family -The Family With the Highest Among-specimentioning
confidence: 99%